Simulação da Energia Cinética Turbulenta (ECT) na Região Nordeste do Brasil em anos de El-Niño e La-Niña - Almeida, Gerson P.; de Sousa, Luis José S.; Junior, João Bosco V. Leal (Ciência e Natura, 2007)
In this work, we perform a numerical evaluation of the turbulentkinetic energy of the semi arid region at the Brazilian Northeast.